Surface sensing and stress-signalling in Ulva and fouling diatoms – potential targets for antifouling: a review. Issue 5 (28th May 2017) - Thompson, Stephanie E. M.; Coates, Juliet C.
Abstract: Understanding the underlying signalling pathways that enable fouling algae to sense and respond to surfaces is essential in the design of environmentally friendly coatings. Both the green alga Ulva and diverse diatoms are important ecologically and economically as they are persistent biofoulers. Ulva spores exhibit rapid secretion, allowing them to adhere quickly and permanently to a ship, whilst diatoms secrete an abundance of extracellular polymeric substances (EPS), which are highly adaptable to different environmental conditions. There is evidence, now supported by molecular data, for complex calcium and nitric oxide (NO) signalling pathways in both Ulva and diatoms being involved in surface sensing and/or adhesion. Moreover, adaptation to stress has profound effects on the biofouling capability of both types of organism. Targets for future antifouling coatings based on surface sensing are discussed, with an emphasis on pursuing NO-releasing coatings as a potentially universal antifouling strategy.